Development of an Innovative Virtual Reality Laboratory Media for Promoting Concepts on the Relation Between Force, Mass, and Accleration of Upper Secondary School Students - Eiamtharachai, Kulaphat; Promratana, Parinda Limpanont (Journal of Education Studies, Chulalongkorn University, 2025)
Experimentation is a key process in promoting scientific conceptual understanding. However, when studying physics concepts related to force and motion, real classroom experiments face several limitations. This research aimed to 1) develop innovative virtual experimental media on the relationship between force, mass, and acceleration, and 2) study the conceptual development of 14 grade 10 students in the science-mathematics program, selected through voluntary sampling. Data collection tools included expert focus group discussions, user focus group discussions, media suitability and consistency evaluation forms, and a two-tier multiple-choice conceptual test. Data analysis revealed that the developed media received an average suitability and consistency rating of 4.41 out of 5.00. The medium was designed as a virtual experiment using a mobile application paired with a headset. It the situation of a spacecraft motion experiment from a second-person point of view. The measurements obtained had an error margin of 5%, offering a realistic experimental experience and enabling effective interpretation of the results. The findings indicated that the media contributed to the development of students’ conceptual understanding. The frequencies of the No Understanding (NU) and Specific Misconception (SM) levels decreased by 18.58% and 2.14%, respectively, while the Partial Understanding (PU) and Sound Understanding (SU) levels increased by 2.14% and 18.58%, respectively.